Analisis dan Perbaikan Proses Bisnis dengan menggunakan Metode Business Process Improvement (BPI) pada PT. Andynni Chitta Sejahtera - Prakoso Adi Bagaskara; Nanang Yudi Setiawan; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT. Andynni Chitta Sejahtera is a company engaged in the field of marine maintenance, especially in sandblasting and painting activities. In carrying out the business process of PT. Andynni Chitta Sejahtera is still experiencing problems and problems in some of its business process activities which are still done manually, which results in activities being worked on for a long time and causing a very high risk of human error. But not all activities that are done manually are problematic, so it is necessary to do an analysis and evaluation of the ongoing business processes. Evaluation and analysis of problems in the Main Business Process was carried out by using Value Added Assessment (VAA) and Root Cause Analysis (RCA) with fishbone diagram techniques. From the results of analysis and evaluation found 2 No Value Added (NVA) activities that can be considered to be eliminated in the recommendation process and there are 9 problematic activities that need to be improved with tools streamlining from the Business Process Improvement (BPI) method. In the last stage, a simulation was carried out by using Bizagi Modeler to find out how much time was lost between business processes (as-is) and the recommended business process (to-be). On the Recommendation of Business Process Service Order Receipts decreased in time by 541.6 minutes, and resulted in a time efficiency of 15.72%. This shows that implementing a business process design recommendation can accelerate the Business Process of Accepting Service Orders.